Monty Python e porta dos fundos: Os processos culturais e o residual no audiovisual contemporâneo - Ramos, Eutália Silva (2017)
The contemporary audiovisual is linked to constant productions that circulate in different media spaces. Much of this comes from the new communication technologies that spread and makes available the content in these spaces. From this, we witness development of multifaceted objects that transit between television and internet. The movement presents us to current processes of intermediality (RAJEWSKY, 2005) and convergence of format, style and language audiovisual productions and remediation. In this way, to observed this as recurring practice in digital culture. However, there is on YouTube old contents that through this practice present news models of organization and production. On this, two groups of humour were identified to represent our study object and two sides of the cultural practices presented in, Porta dos Fundos (2013) and Monty Python (1969). Different cultures, models of production and especially in their circulation technology, we find both are part of the same cultural environment today and act similarly on YouTube. In order understand this cultural phenomenon and the relation between them, we discovered residual culture (WILLIAMS, 1970; JENKINS, FORD, GREEN, 2014) a basics for our analysis. We carried out a comparative study between three sketches of the groups “Spam” and “Rola”, “Job Interview” and “Job Interview”, and “Birth” and “Oh, My God!”. In the results of this research, residues in format, language, narrative structure and style were. We verified that sketches analyzed are part of current audiovisual production, which seek reference in residues of a nostalgic style which have meanings and values.